Let’s Judge a Book by its Cover: The Case Study of Active Skills for Reading - Mahdis Mousavi; Mansoor Ganji; Khaled Kordi Tamandani (Journal of Modern Research in English Language Studies)
Textbook is an essential element of teaching and learning materials. After the teacher, textbooks are the most important factor in learning. Since textbooks act as an important material in teaching and learning, they need to be evaluated regularly. In the light of the foregoing, this study aimed to evaluate “Active Skills for Reading” using a researcher-made checklist and a structured interview. This book was being taught in six classes of Chabahar Maritime University as a general English coursebook. The goal of this study was to determine the suitability of the book as a general English course from the students’ and teachers’ perspectives. To this end, 150 students and 4 teachers were selected, and data were collected during two semesters in 2020. The quantitative data of the checklist were analyzed by calculating descriptive statistics using SPSS version 26, and qualitative data was analyzed through deductive content analysis. It was shown that the teachers and students believed that the appearance of the book is attractive, the content of the book is up-to-date and practical, and the goals are well defined. It was also revealed that although the textbook had some shortcomings such as lack of enough grammar sections in each unit, teachers felt the book was still appropriate for general English courses, especially for developing the reading skills. Generally, it was indicated that the textbook had met students’ needs for a general English course. The study ends with suggestions for general English teachers and materials designers.